The Wadi Zaghra metasediments of Sinai, Egypt: new constraints on the late Cryogenian–Ediacaran tectonic evolution of the northernmost Arabian–Nubian Shield - Andresen, A.; El-Enen, M.; Stern, R.; Wilde, Simon; Ali, K.A. (Taylor & Francis Inc., 2014)
The depositional age of the Wadi Zaghra metasediments (Zaghra Formation) of the Sa’al-Zaghra metamorphic complex (Sinai) in the Arabian–Nubian Shield (ANS) has been constrained by LA-ICP-MS dating of zircons from (1) metaconglomerate granitoid clasts, (2) the metaconglomerate matrix, (3) biotite-schist, and (4) diorites and granites intruding the metasediments. Three granitoid boulders from a metadiamictite of the Zaghra Formation give crystallization ages of 651 ± 3, 647 ± 3, and 640 ± 4 Ma respectively. Detrital zircon age populations from laminated siltsones and conglomerate matrix vary somewhat with stratigraphic position, a variation best explained by changes in depositional environment and source area with time. Three distinct zircon age populations are identified in the matrix; at ca. 1000, 750, and 630 Ma, with less pronounced peaks at ~780 and ~800 Ma. The youngest detrital zircons indicate deposition after 630–625 Ma. The emplacement age of the post-depositional intrusives is enigmatic due to a large population of xenocrystic zircons, but is interpreted to be as old as ca. 615 Ma. This implies deposition and deformation of the Zaghra Formation in the time interval 625–615 Ma, thus older than the inferred depositional age of the Hammamat deposits in the Eastern Desert of Egypt, which is commonly correlated. The inferred depositional age is similar to the deposits in nearby Rutig Basin, where conglomerates were deposited in two pulses; at ca. 620–610 and 600–590 Ma. The appearance of late Mesoproterozoic (ca. 1.1 to –1.0 Ga) detrital zircons in the fine-grained laminated matrix facies of the Zaghra Formation demonstrates that ~1.0 Ga basement rocks (Sa’al terrane?) were exposed when Zaghra basin sediments were being deposited.